2003
DOI: 10.1021/pr030003l
|View full text |Cite
|
Sign up to set email alerts
|

Processing of Serum Proteins Underlies the Mass Spectral Fingerprinting of Myocardial Infarction

Abstract: The MALDI-TOF spectra of peptides from the sera of normal and myocardial infarction patients produced patterns that provided an accurate diagnostic of MI. In myocardial infarction, the spectral pattern originated from the cleavage of complement C3 alpha chain to release the C3f peptide and cleavage of fibrinogen to release peptide A. The fibrinogen peptide A and complement C3f peptide were in turn progressively truncated by aminopeptidases to produce two families of fragments that formed the characteristic spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
338
2
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(356 citation statements)
references
References 49 publications
14
338
2
2
Order By: Relevance
“…Marshall et al have recently shown that when plasma was left sitting at room temperature for 4 or 8 h, the MALDI-TOF spectra, as recorded by a SELDI-TOF instrument, changed significantly, suggesting that many peptides were generated by proteolytic digestion ex vivo (59). The authors attributed this peptide generation to action of specific (serine) proteases, because they could block this effect with serine protease inhibitors.…”
Section: Technical Caveats and Methodological Detailsmentioning
confidence: 99%
“…Marshall et al have recently shown that when plasma was left sitting at room temperature for 4 or 8 h, the MALDI-TOF spectra, as recorded by a SELDI-TOF instrument, changed significantly, suggesting that many peptides were generated by proteolytic digestion ex vivo (59). The authors attributed this peptide generation to action of specific (serine) proteases, because they could block this effect with serine protease inhibitors.…”
Section: Technical Caveats and Methodological Detailsmentioning
confidence: 99%
“…Of the 66 cases of nonmalignant disease, 63 were recognized as not cancer. This result yielded a sensitivity of 100%, specificity of 95% (87)(88)(89)(90)(91)(92)(93)(94)(95)(96)(97)(98)(99), and PPV of 94% (101). Although the limitations of this study design and its analysis have been discussed in some detail in the literature (103)(104)(105)(106), the potential implications of such proteomic spectrum analysis for the identification of novel tumor markers is huge.…”
Section: Trials In the Generalmentioning
confidence: 95%
“…Serum apo A-I, apo A-II, and their glycosylated products were found differentially expressed between atherosclerosis patients and normal controls by using SELDI-MS [249]. MALDI-MS analysis of peptides from the sera of normal and AMI subjects produced characteristic patterns that could provide an accurate diagnosis of AMI [250]. Serum alpha-B-crystallin and tropomyosin were discovered and validated as valuable biomarkers for cardiac allograft rejection [251].…”
Section: Application To Human Disease Detectionmentioning
confidence: 99%